Desigualdades de gastos em saúde: relação entre saúde e renda durante a pandemia - Barros, Luiz Alexandre Moreira (2023)
The objective of the work is to study alternative resources such as regions and individuals most affected by the pandemic. The inequality of supply and demand is evident, before and during the pandemic, on the consumption of different types of individuals. Therefore, the influence of the impact of the public system on the saturation of the health system is modeled through a decentralized computational equilibrium (DCE). The results found indicate that the supply of goods by the state softens the impact of the pandemic on the poorest individuals and reduces inequality between social classes and the different regions of the parents.